Covid-19 research in Bangladesh: A scientometric analysis during 2020-23 - Gupta, B. M.; Kappi, Mallikarjun; Walke, Rajpal; Bansal, Madhu (Iberoamerican Journal of Science Measurement and Communication, 2023)
Objective. We examined the bibliometric characteristics of 3616 Bangladesh’s publications on Covid-19 during 2020-2023. For this purpose, we used quantitative and qualitative bibliometric indicators. Design/Methodology/Approach. Bangladesh publications on Covid-19 during 2020-2023 were retrieved using the Scopus database. From each record, we retrieved data on the title, author, organizations, journal, publication type and source, country, collaboration, funding, topic and keywords. They were exported to MS-Excell for bibliometric analysis, and VOSviewer software was used for analyzing keyword co-occurrence networks. Results/Discussion. The Bangladesh-related Covid-19 papers in the Scopus database constitute 3616 papers, which hold 50th global rank with 0.75% share in global output and registered 14.63 average citations per article (CPP). The 732 (21.52%) out of 3616 Bangladesh papers attracted external funding support, and 2493 (72.28%) have participated in international collaboration. The U.K., USA, India and Saudi Arabia contributed the most to Bangladesh’s international collaborative papers. The University of Dhaka, Jahangirnagar University, North South University and Daffodil International University were the most productive organizations. In contrast, CHINTA Research, Khulna University of Engineering & Technology, Jahangirnagar University and Jashore University of Science & Technology registered the highest impact. The most preferred communication channels were PLOS One, Heliyon, Frontiers in Public Health and Annals of Medicine & Surgery. The Asian Journal of Psychiatry, IEEE Access, Science of the Total Environment and BMJ Global Health registered the highest citations. Clinical studies were the most frequent category, followed by epidemiology, risk factors and diagnosis. In contrast, adults and the middle-aged formed the largest population age groups, followed by aged, children and adolescents. Conclusion. The bibliometric analysis of Covid-19 research has evolved global interest, including in Bangladesh. For the first time, the present study throws light on the current status and publication trends of research and development efforts in Bangladesh.